PEMBERDAYAAN PETANI SAYURAN MELALUI PENERAPAN PENGENDALIAN HAMA DAN PENYAKIT TANAMAN BERBASIS EKOLOGI DI KECAMATAN ADILUWIH, KABUPATEN PRINGSEWU - Puji Lestari; Yuyun Fitriana; Selvi Helina; Ivayani Ivayani; Luna Lukvitasari; Ni Kadek Emi Sintha Dewi; Tri Maryono; Radix Suharjo (Universitas Mataram, 2026)
Adiluwih Subdistrict, Pringsewu Regency, is recognized as an important area for horticultural and food crop production in Lampung Province. However, current farming practices in this region continue to experience substantial pressure from plant pest organisms, alongside a heavy reliance on synthetic chemical pesticides for crop protection. This community service program aimed to enhance farmers’ capacity to adopt ecologically based approaches to pest and disease management that are environmentally sound and sustainable. The activities were implemented through participatory extension sessions, field-based demonstrations, and continuous mentoring of farmer groups. Training materials focused on the identification of major insect pests and their natural enemies, the application of biological control agents, the establishment of refugia plants, and the use of alternative control tools such as pheromone traps and yellow sticky traps. The program resulted in a marked improvement in farmers’ understanding of ecologically based pest management principles, as indicated by an increase in the mean knowledge score from 56.36 at baseline to 93.64 after program implementation, representing a 61.16% improvement. In addition, farmers successfully adopted ecological practices on demonstration plots, including refugia planting and trap installation, which contributed to a reduction in pest populations. The program also strengthened farmer group institutions through sustained guidance in agribusiness-oriented farm management. Overall, this community engagement initiative not only enhanced farmers’ technical capacity to implement environmentally friendly pest management practices but also supported the development of more sustainable agricultural systems in the Adiluwih area.